Variability and assessment of interrelationships among yield and yield-related characters of pea accessions under the influence of high temperature - Zanetta, Chindy Ulima; Rafii, Mohd Y.; Jaafar, Juju Nakasha; Warkentin, Thomas D.; Waluyo, Budi; Ramlee, Shairul Izan (Taylor and Francis Group, 2023)
Understanding the response and variability of pea accessions traits to high temperatures is an excellent strategy for breeding pea for heat tolerance. This research aimed to determine character variability and interrelationships among yield and yield-related traits as responses to pea grown under daily high temperature. Ninety-four pea accessions were grown under greenhouse conditions in Malaysia and Indonesia in the 2020–2021 season. During flowering up to the physiological maturity stage, the average daily maximum temperature was 31.6°C–32.4°C in Malaysia and 26.5°C–27.6°C in Indonesia. Heat stress reduced grain yield in Malaysia by 40% when the daily maximum temperature was above 32°C compared to yield in Indonesia. The number of seeds per pod, number of seeds per plant, filled pods per plant and number of ovules per pod were positively correlated with grain yield in Malaysia and Indonesia, respectively. A negative correlation was observed for percent aborted flower and aborted seed with grain yield. The genotype by trait biplot identified accessions B32, A19, G76, A11 and D44 as potentially promising under high-temperature conditions with high yield supported by plant height.